ChemInform Abstract: Polymorph Engineering of TiO2: Demonstrating How Absolute Reference Potentials Are Determined by Local Coordination. Issue 31 (August 2015) - Buckeridge, John; Butler, Keith T.; Catlow, C. Richard A.; Logsdail, Andrew J.; Scanlon, David O.; Shevlin, Stephen A.; Woodley, Scott M.; Sokol, Alexey A.; Walsh, Aron
Abstract A multiscale quantum‐chemical approach is used for examining the electronic structure of eight known TiO2 polymorphs and aligning their ionization potential and electron affinity relative to an absolute energy reference.